Innovative Characteristics of Education Quality Management in Professional Educational Institutions - Ismatillayevna, Khalmukhamedova Rushana (International Journal on Integrated Education, 2023)
This article presents the management of innovative processes in professional educational institutions, a new strategy for the establishment and development of the continuous education system, and the tasks of innovative education.